Mothers and Daughters in Ismat Chugtai's Writings. Issue 1 (June 2016) - Farooqi, Baran; Tiwari, Kusha
This article delves into the discourse of motherhood and the girl-child as deconstructed by Ismat Chughtai in A Life in Words (2012) and The Crooked Line (2003). These two works due to their intertextual connections and thematic similarities become appropriate tools for analyzing Ismat's concern with femininity as a complex web of tangible relations. Ismat's women, even though living cloistered lives exert their individuality and authority in discursive ways. The girl-child narrator in both these works is a spectator to the wiles that women employ to empower themselves in the male dominated society. In these two works, Ismat unscrupulously deconstructs the images of the sacrificing mother and the dutiful daughter that are ingrained within the patriarchal system. In the process she liberates the experience of motherhood from age-old categories and gives voice to hidden anger, angst and discontent in the mothering self. At the same time Ismat also destabilizes the stereotypical image of the girl-child who not only acquires a certain subject position but also challenges motherly domination and familial authority. Thus both Shaman and young Ismat devalue and delegitimize the figure of the ideal daughter as exhibited in the polished conduct of Bari Apa and Manjhu (Shaman's elder sisters). In deconstructing these established discourses, Ismat is also creating new ones that recognize alternative subject positions for women.